EXCLUSION CLAUSES” OF THE UNHCR STATUTE AND THE CONVENTION RELATING TO THE STATUS OF REFUGEES - Soeprapto, Enny (Indonesian Journal of International Law, 2010)
The Statute of the Office of the United Nations High Commissioner for Refugees (UNHCR Statute) not only defines the persone materiae of the competence of the United Nations High Commissioner for Refugees (High Commissioner) but also stipulates circumstances under which the competence of the High Commissioner shall cease or shall not apply to such persons. The Convention relating to the Status of Refugees (CSR) contains similar provisions. The provisions on the non-extension of the High Commissioner’s competence under the UNHCR Statute and the non-applicability of the CSR to certain categories of persons are commonly referred to as “exclusion clauses”. This article tries to make some modest observations on such “exclusion clauses” and their legal implications.